2014
DOI: 10.1146/annurev-food-030713-092415
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy in the Food Industry

Abstract: Despite advances in modern technologies, the food industry is continuously challenged with the threat of microbial contamination. The overuse of antibiotics has further escalated this problem, resulting in the increasing emergence of antibiotic-resistant foodborne pathogens. Efforts to develop new methods for controlling microbial contamination in food and the food processing environment are extremely important. Accordingly, bacteriophages (phages) and their derivatives have emerged as novel, viable, and safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
169
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(187 citation statements)
references
References 120 publications
0
169
0
7
Order By: Relevance
“…In a previous study, it was showed that bacteriophage proteins were capable of lysing C. perfringens and could be expressed in yeast and added as lysates to animal feed to reduce the bacterium to improve health and food safety for monogastrics animals during production (Miller et al, 2010). The host-specificity role of bacteriophages (Endersen et al, 2014) can be considered as a positive feature of phage therapy because they only infect bacteria which have the membrane receptor. Tail penetration through cell walls degraded enzymatically drives insertion of phage DNA into the cytoplasm of the host to encode specific enzymes and proteins by the phages genome in order to lyse host cell (Endersen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was showed that bacteriophage proteins were capable of lysing C. perfringens and could be expressed in yeast and added as lysates to animal feed to reduce the bacterium to improve health and food safety for monogastrics animals during production (Miller et al, 2010). The host-specificity role of bacteriophages (Endersen et al, 2014) can be considered as a positive feature of phage therapy because they only infect bacteria which have the membrane receptor. Tail penetration through cell walls degraded enzymatically drives insertion of phage DNA into the cytoplasm of the host to encode specific enzymes and proteins by the phages genome in order to lyse host cell (Endersen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The host-specificity role of bacteriophages (Endersen et al, 2014) can be considered as a positive feature of phage therapy because they only infect bacteria which have the membrane receptor. Tail penetration through cell walls degraded enzymatically drives insertion of phage DNA into the cytoplasm of the host to encode specific enzymes and proteins by the phages genome in order to lyse host cell (Endersen et al, 2014). Another experiment with humans showed that prophylactic phage therapy of Clostridium difficile infection can considerably reduce the burden of C. difficile vegetative cells and caused a clinically relevant decrease in toxin production (Meader et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These broad-spectrum approaches also kill potentially beneficial bacteria that are important components of foods. In contrast, the bacteriophages offer an environmentally safe, non-corrosive and effective modality for eliminating or significantly reducing the levels of their specifically targeted bacterial pathogens in various foods, without a deleterious impact on the organoleptic properties and without disrupting the normal and often beneficial microflora of foods (Endersen et al, 2014;Hagens and Offerhaus, 2008;Tan et al, 2014).…”
Section: Foodborne Illnessesmentioning
confidence: 99%
“…Thus, as Campylobacter sp., Salmonella sp. and Listeria monocytogenes are not commonly associated with livestock contamination, researchers have focused largely on reduction of these bacteria in poultry, fresh or processed foods by direct application of phages onto contaminated foods (Endersen et al, 2014).…”
Section: Control Of Food-borne Pathogens In Animalsmentioning
confidence: 99%
“…21 and be important in food safety and productivity. 22 For example, phages that kill Paenibacillus, a serious problem in the honeybee industry, have been found. 23 Unique endolysins that kill bacteria could play a major role in human and animal health and in food safety.…”
Section: Student Discoveries Must Be Significant and Continue To Be Umentioning
confidence: 99%